SYSTEMIC FUNCTIONAL LINGUISTIC STUDY ON WEST LOMBOK REGENTâS SPEECH - Usman, Hakim (International Journal of Systemic Functional Linguistics, 2017)
This research is focused on analyzing transitivity system and interpersonal meaning in West Lombok regentâs speech and the the research relevance to discourse learning in schools. It is aimed at describing the system of transitivity and interpersonal meaning in speech and describing realized meaning or value in the dominant process and basic action with their relevance to discourse learning in schools. The investigation is, in addition, carried on with the orientation of LFS theory by Halliday focusing on text, particularly, texts of Speech of West Lombok regent. In addition, the research carried on by using descriptive qualitative research approach. Data collected through employing of the methods of documentation, observation, and record technique. The results showed that the dominant process realized in texts of Speech of West Lombok regent is mental process with range percentage 21% and the dominant basic action is the statement action with range of percentage 60%. Types of values found in the texts are value of awareness, sincerity, confidence, certainty (direction), creativity, thoroughness, responsibility, compliance, and permissive value. The values of basic action statement found in the texts, particularly, are value of gratitude, awareness, sincerity, and dedication. The relevance of this research to discourse learning in schools shows the relationship between language and approaches that can be described explicitly, where learning discourse, especially speech, at the school level can also be researched using SFL (Systemic Functional Linguistic) theory approach to find out the meaning exist in it, such as research conduction in the college.